2021
DOI: 10.3390/ijms22157804
|View full text |Cite
|
Sign up to set email alerts
|

Skin Wound Healing Rate in Fish Depends on Species and Microbiota

Abstract: The skin is a barrier between the body and the environment that protects the integrity of the body and houses a vast microbiota. By interacting with the host immune system, the microbiota improves wound healing in mammals. However, in fish, the evidence of the role of microbiota and the type of species on wound healing is scarce. We aimed to examine the wound healing rate in various fish species and evaluate the effect of antibiotics on the wound healing process. The wound healing rate was much faster in two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Wound healing in fish is a complex process that can demand days, weeks, or even months to complete, depending on the type and size of wound, the wound's location on the body, the species of fish in question, infection occurrences, suture type and retention, and environmental temperatures (Jepsen et al 2002; Caputo et al 2009; Ceballos‐Francisco et al 2017; Schoonyan et al 2017; Sveen et al 2020; Yun et al 2021). We echo concerns previously raised by others (e.g., Gilliland 1994; Jepsen et al 2002) that gut sutures may be inappropriate in situations where the suture is likely to be absorbed or shed before wound healing is complete.…”
Section: Discussionmentioning
confidence: 99%
“…Wound healing in fish is a complex process that can demand days, weeks, or even months to complete, depending on the type and size of wound, the wound's location on the body, the species of fish in question, infection occurrences, suture type and retention, and environmental temperatures (Jepsen et al 2002; Caputo et al 2009; Ceballos‐Francisco et al 2017; Schoonyan et al 2017; Sveen et al 2020; Yun et al 2021). We echo concerns previously raised by others (e.g., Gilliland 1994; Jepsen et al 2002) that gut sutures may be inappropriate in situations where the suture is likely to be absorbed or shed before wound healing is complete.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of wound healing in fish have shown that wound type (mechanical versus ulcer‐inducing pathogens), location on the body, water quality, and mucosal immune factors (Ceballos‐Francisco et al 2017; Sveen et al 2020) can all play a role. Recently, species differences in wound healing were related to habitat, skin types, and the associated microbiome (Yun et al 2021). Further research will be needed to identify factors that may influence the SMB microbiome and healing of dermal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…All fish in the immersion challenge received a skin wound based on the results from the pilot experiments. Skin wounds were induced following the methods described in Yun et al (2021) using a 4 mm‐diameter skin biopsy punch (Kai® Medical, Japan). The induced skin wound removed the epidermis and dermis of the skin, exposing subcutaneous tissue.…”
Section: Methodsmentioning
confidence: 99%